"Marmur", "morena czołowa", "kamień polny", "kamień reński", "piaskowiec czerwony i biały", "węgiel brunatny"...Kamienie Zielonej Góry. Zielona Góra kamieni. Kilka lit(h)olingwistyczno-kulturologicznych uwag o kamieniach spotykanych w różnych przestrzeniach Winnego Grodu utrwalonych w wybranych współczesnych przewodnikach po Ziemi Lubuskiej = "Marble", "terminal moralne", "field stone", "rhinestone", "red and white sandstone", "brown coal"... Stones of Zielona Góra. Zielona Góra of stones. A few lit(h)olinguistic-culturological remarks on stones in the City of Wine preserved in selected contemporary Ziemia Lubuska region guidebooks - Węgorowska, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The lit(h)olinguistics reflection focuses on stones and names relating to stones present in the City of Magpies' various open and closed spaces. The relation "space - city - stone" became an inspiration to comment on multiple stones found in Zielona Góra in, among others: a) landscape ("terminal moraine", "brown coal", "memorial stone", "lapidarium"), b) secular architecture ("city walls made of fieldstones", "sidewalk", "stone foundations"), c) sacral architecture ("medieval stone chapel in a vineyard", "keystones", "rococo stone baptismal font"), d) museum ("shaming heavy Stones"), e) jeweller company ("amber", "pearl", "coral"). Stones, which spatially embellish Zielona Góra, and their names were listed and interpreted in the text. They make the City of Wine the urban phenomenon, into which palimpsest layers the stone elements of nature and culture have permanently inscribed themselves.
Keywords: kamienie; przestrzeń; miasto; Zielona Góra; lit(h)olingwistyka; stones; space; city; lit(h)olinguistics